Evaluación de pérdidas poscosecha de maracuyá (Passiflora edulis) producidas en la parroquia San Isidro y comercializadas en la ciudad de Guayaquil - López Cornejo, María Leonor (2015)
The present research aimed to assess the postharvest losses of passion fruit (Passiflora edulis) produced in the parish of San Isidro. For the affection is conducted interviews, surveys to small and large producers; in the collection centers and points of marketing. Working with a total of 300 farms, these took a substantial sample of 73 farms producing to perform the research and evaluate the harvest losses that occurs through marketing, So note the causative factors of physical loss; where it was obtained as a result the following: manual collection 7.95 %, transport (mules, vehicles) 7.93 %, and in marketing with a percentage of 10.85 %. Within the chain of production and marketing are showed losses in transportation led to the city of Guayaquil, producing companies to nectars and terminal of transfer of food, were identified where losses of $126,260.42. For the economic valuation losses could be obtained within the collection with $ 8,176.00. Also was able to appreciate the losses in the carriers, from the center of hoards until the city of Guayaquil which strifes of stacked with $92,173.03. It was concluded that the greater harvest losses is given in stage of the marketing with an average of 10.85 % with respect to valuation of $ 126,260.42 without forgetting that the total of the physical losses in all the evaluated stages in this research work was a 26.73 %.